A Study of the Competitiveness of Regions based on a Cluster Analysis: The Example of East Germany - Franz Kronthaler (European Regional Science Association (ERSA), 2003)
The Eastern enlargement of the EU is likely to increase the regional disparities within the EU. At the same time regional cohesion is a primary objective of EU economic policies. This raises the question of whether and when the regions of the accession countries will reach the average economic level of the EU. East Germany is used as an instructive example of a transition country for the integration process of the new Central and Eastern European member states. The objective of this study is to analyse whether some East German regions have the same economic capability by now as the regions in West Germany so that they are on a competitive basis with the West German regions and are able to reach the same economic level in the long run. If this is not the case, it is important to know more about the reasons for the economic weakness of the East German regions twelve years after unification. The study is based on a cluster analysis. Criteria for the cluster formation are several economic indicators, which provide information about the economic capability and their determinants. The choice of the indicators is based on a review of results of the theoretical and empirical literature on the new growth theory. The results show that most of the East German regions have not yet reached the economic capability and the competitiveness of their West German counterparts so that they - from the viewpoint of the new growth theory - are not in the position to reach the same economic level. According to this theory economic disadvantages are most notably the consequences of less technical progress, a lack of entrepreneurship and fewer business concentration. Under these points it is especially noteworthy that young well educated people leave these East German Regions so that human capital will be in the near future also a bottle-neck. Only a few regions in East Germany - those with important agglomerations - are comparable to those West German regions with average cabability and competitiveness, but not to those with economic capability and competitivness above average. Even those more advanced East German Regions suffer from economic disadvantages as less technical progress and low business concentration. There are important policy implications based on these results: regional policy funding in East Germany was not able to assist raising all regions to a sufficient level of competitiveness. It may be more effective to concentrate the regional policy funding on a selection of important agglomerations. This has also strong implications for the EU regional policy assuming that the accession countries will have similar problems in catching up to the economic level of the EU as have the East German regions. Keywords: Regional Disparities, Competitiveness, Cluster Analysis, East Germany, EU-Enlargement JEL classification: R12; P52; O18
Keywords: 330